Analisis dan Pemetaan Sebaran Polutan CO, CO2, PM10, dan VOCs di Perkantoran Petikemas - Putri Amelia Nur Widyastuti; Widya Nilandita; Amrullah Amrullah (Buletin Keslingmas, 2026)
Indoor air quality in office buildings plays a crucial role in human life as it directly impacts the health and productivity of building occupants. This study aims to assess indoor air quality and compare it with Ministry of Health Regulation No. 48 of 2016, examine the relationship between temperature and humidity on indoor air pollutants, and map the distribution of CO, CO2, PM10, and VOC concentrations in staff rooms. The analytical methods used include descriptive analysis, quantitative analysis using the Spearman correlation test, and spatial analysis using Surfer 16. The results of the study indicate that several parameters, such as temperature, humidity, light intensity, CO₂, and PM10, do not meet quality standards at most points. However, for CO and VOCs, concentrations were found to be significantly below quality standards. The Spearman correlation test showed a significant relationship between temperature and VOCs with a p-value of 0.021<0.05 and a correlation coefficient of -0.467, indicating a negative relationship with a moderate level of strength. The distribution mapping results are shown in red for areas with high concentrations or those not meet quality standards, while green indicates areas with concentrations below quality standards. This is an important step in evaluating and developing ventilation and lighting systems, as well as maintaining indoor air quality in accordance with established standards.